Antibacterial Activity of Ethanol Extract of Red Betel Leaves (Piper crocatum) Against Propionibacterium acnes - Sihombing, Angelina Victoria; Rini, Desi Indria; Woda, Rahel Rara; Amat, Anita Lidesna Shinta (Jurnal Biologi Tropis, 2026)
Propionibacterium acnes is a type of bacteria that typically exists on skin areas with many sebaceous glands, like the scalp and face. The exploration of natural antibacterial agents made from herbal plants is one approach to decrease resistance issues. One such plant utilized is red betel, scientifically known as Piper crocatum. The objective of this study is to assess the antibacterial properties of the ethanol extract from red betel leaves against Propionibacterium acnes. This study adopted a true experimental framework with a post-test only control group model. The red betel leaf extract was produced through maceration using a 70% ethanol solution, followed by evaporation until a concentrated extract was achieved. In this study, the treated groups included various concentrations: 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, and 1.56%, alongside a positive control using clindamycin and a negative control using sterile aquades. The antibacterial testing was performed using the disc diffusion method, referred to as the Kirby-Bauer technique against Propionibacterium acnes bacteria. The analysis conducted was the One Way Anova statistical test. Findings from this study reveal that the extract of red betel leaves contains alkaloids, tannins, saponins, flavonoids, and terpenoids. The testing outcomes indicate that the average diameter of the inhibition zone resultant from each sample is 11.16 mm for the 100% concentration, 9.63 mm for the 50% concentration, 8.85 mm for the 25% concentration, 8.21 mm for the 12.5% concentration, 7.78 mm for the 6.25% concentration, 6.93 mm for the 3.125% concentration, and 0 mm for the 1.56% concentration. From the results, it can be concluded that the ethanol extract from red betel leaves exhibits antibacterial activity against the growth of Propionibacterium acnes.